2014
DOI: 10.1002/clc.22343
|View full text |Cite
|
Sign up to set email alerts
|

Is High‐Intensity Statin Therapy Associated With Lower Statin Adherence Compared With Low‐ to Moderate‐Intensity Statin Therapy? Implications of the 2013 American College of Cardiology/American Heart Association Cholesterol Management Guidelines

Abstract: Background:The recent cholesterol guideline recommends high-intensity statins in cardiovascular disease (CVD) patients. High-intensity statins are associated with more frequent side effects. Therefore, it may be of concern that these recommendations might reduce statin adherence. Hypothesis: High-intensity statins are associated with lower adherence compared with low-to moderateintensity statins. Methods: In a national database of 972 532 CVD patients from the Veterans Health Administration, we identified pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 23 publications
3
46
0
1
Order By: Relevance
“…However, using VA database we have previously shown that there is minimal reduction in statin adherence (of unknown clinical significance) when using high-intensity compared to low-moderate intensity statin therapy. 7 Most recent cholesterol guidelines recommend a “treat to risk” approach with a fixed dose using moderate to high intensity statin therapy in patients with diabetes and recommend that there is not enough evidence to use non-statin lipid lowering therapy in most patients. 3 Following contemporary lipid guidelines during our study period when the focus was “treat to LDL-C target” (goal LDL-C <100 in high risk and <70 mg/dL in very high risk patients, such as those with CVD), 1720 providers may have elected not to use statin therapy in those who were already at their LDL-C goal or to use non-statin lipid lowering therapy only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, using VA database we have previously shown that there is minimal reduction in statin adherence (of unknown clinical significance) when using high-intensity compared to low-moderate intensity statin therapy. 7 Most recent cholesterol guidelines recommend a “treat to risk” approach with a fixed dose using moderate to high intensity statin therapy in patients with diabetes and recommend that there is not enough evidence to use non-statin lipid lowering therapy in most patients. 3 Following contemporary lipid guidelines during our study period when the focus was “treat to LDL-C target” (goal LDL-C <100 in high risk and <70 mg/dL in very high risk patients, such as those with CVD), 1720 providers may have elected not to use statin therapy in those who were already at their LDL-C goal or to use non-statin lipid lowering therapy only.…”
Section: Discussionmentioning
confidence: 99%
“…We used ICD 9-CM diagnoses and procedure codes as well as current procedural terminology codes to identify CVD and other variables (Online-only Supplemental Table) as described in previous studies. 7,8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified insulin use through filled prescriptions. ICD‐9‐CM diagnosis and procedure codes were used along with procedure terminology codes to identify presence of CVDs (ischemic heart disease, peripheral arterial disease, or ischemic cerebrovascular disease) as described in prior studies …”
Section: Methodsmentioning
confidence: 99%
“…We used patient‐level variables to calculate Diagnostic Cost Group (DCG) relative risk scores (RRS), which serve as an indirect measure of a patient's overall illness burden. DCG RRS has been used and validated in prior studies as a surrogate marker for disease burden . A patient with a DCG RRS score of 1.5, for example, reflects a 50% greater expected cost of care compared with an average patient (DCG RRS score = 1), reflecting a 50% greater disease burden.…”
Section: Methodsmentioning
confidence: 99%